Aplikasi Fuzzy Inference System untuk Menentukan Lokasi Pengembangan Sentra Peternakan Rakyat (SPR) Sapi Potong di Kabupaten Jember - Bambang Heri Purnomo; Yuli Wibowo (Agroindustrial Technology, University of Trunojoyo Madura, 2018)
The development of community farming center (SPR) of cattle beef to consolidate the potential of people's cattle beef to be managed optimally to increase the production and welfare of farmers in realizing national beef self-sufficiency. Jember Regency as one of the centers of cattle beef in East Java Province has a policy to develop SPR in a number of sub-districts but still faces a number of problems that is determining which district will be chosen as SPR location. This research aims to design the model of determining SPR cattle beef location using fuzzy inference system technique. A number of key criteria in location determination are explored then designed into decision support models using the Matlab fuzzy tool box. The results showed that there are three key criteria for determining the location of SPR development of cattle beef, namely 1) potential Feed from plants; 2) population of cattle beef; and the availability of facilities and infrastructure. Decision support model is built with fuzzy inference system technique using Triangular Fuzzy Number (TFN) representation model and MAMDANI inference method. The number of rules built as many as seven rules with the operator or and and and. Model simulation results show that the locations that are categorized as Very Suitable for SPR development of cattle beef are Silo, Sumberjambe, and Ledokombo Subdistricts, While sub District Gumukmas, Sumberbaru, Puger, Wuluhan, Kencong, Bangsalsari, Mumbulsari, and Jenggawah, fall into the Suitable category.